Sistem Pendukung Keputusan Pemilihan Laptop pada Toko Online dengan Metode Fuzzy Tahani - Syahroni, Abd Wahab; Rachmatullah, Sholeh (Sinkron : jurnal dan penelitian teknik informatika, 2018)
The research in this paper is a study of the best laptop recommendations on laptop online stores using fuzzy methods. The fuzzy method used is the fuzzy database model of the tahani model with two variables, fuzzy and non-fuzzy variables with fire strength calculations using AND or OR logic. The criteria for fuzzy variables used include price, LCD, hard disk, memory, processor, and warranty. The criteria for non-fuzzy input variables consist of whether or not there are laptop facilities such as wifi, bluetooth and camera, while the membership functions used are triangular and shoulder-shaped curves. The first step is that the user chooses fuzzy data input, in fuzzy data input, the user is required to choose at least three variables, namely the hard disk, memory and processor variables. The price variable, screen (LCD) and warranty are optional (can be selected or not). For non fuzzy input variables are also optional. After that, the process of calculating the degree of membership of the fuzzy variable will be carried out based on the reference curve, then doing fire strength calculations using AND or OR logic, so that the best laptop recommendations are produced that match the user's choice criteria. From the results of the experiment showed that the application of fuzzy database method of tahani model was proven to produce laptop recommendations that match the criteria desired by the user as evidenced by the Likert scale of 72%, which means that the user or consumer agrees if the fuzzy database model of this model is applied to the store online laptop.